Toxic and sublethal effects of buprofezin on the whitefly parasitoid Encarsia formosa Gahan - Drobnjaković, Tanja; Marčić, Dejan; Prijović, Mirjana; Milenković, Slobodan (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2020)
Acute toxicity of a buprofezin-based product (commercial product Elisa 440 SC) to pupae ofthe whitefly parasitoid Encarsia formosa Gahan (Hymenoptera: Aphelinidae), and its effects on lifehistory traits and population growth in F1 generation of a commercial strain (“Dutch” strain, D)and two local populations from Serbia (Bujanovac, B; Negotin, N) were examined in laboratorybioassays. All trials were carried out at 27±1°C temperature and 60±10% relative humidity, andunder 16/8 h daylight/darkness photoperiod in four replications. In an acute toxicity bioassay,tobacco leaves carrying parasitoid pupae (20 pupae per replicate) were treated with a series ofbuprofezin concentrations covering a 10-90% mortality range, and mortality was calculatedbased on the number of emerging adults 9 days after treatment. The following LC50 (mg/l)estimates were obtained: 244.2, 281.5 and 199.5 (for B, N and D, respectively). The productbased on buprofezin, applied to parasitoid pupae at concentrations within the LC50s and 95%confidence limits (264 mg/l for B and N; 220 mg/l for D), significantly prolonged the durationof juvenile development (2, 1.7 and 2.2 days for B, N and D, respectively, compared to controldata). Females from all tested populations that emerged from the treated pupae and wereexposed to the residual action of buprofezin lived shorter than control females (B, N and D by1.5, 0.7 and 1.7 days, respectively). Also, females that emerged from the treated pupae achieveda significantly reduced level of parasitism (B, N and D by 11.7, 17.7 and 17.6 %, respectively), totaladult emergence (B, N and D by 11.6, 17.8 and 17.8 %, respectively) and instantaneous rate ofincrease (B, N and D by 8.2, 6.8 and 12.5 %, respectively), compared to control. More precisedetermination of risks involved in the use of buprofezin requires its more detailed field testing.
Keywords: Encarsia formosa; buprofezin; sublethal effects; life history traits; population growth